Analisis Pembukuan Sederhana terhadap Pengelolan Cashflow UMKM di Desa Ciangsana, Kecamatan Gunung Putri, Kabupaten Bogor - Nurhasan Nurhasan; Rico Septia B (J-MAS (Jurnal Manajemen dan Sains), 2023)
Micro, Small and Medium Enterprises are one of the pillars of the people's economy in which most small and medium entrepreneurs come from family or home industries. This study aims to find out and analyze how the influence and application of simple bookkeeping has on cash flow management in MSMEs in the Ciangsana Village environment. The research method used in this study is a mixed methods research method and the research design to be used is a concurrent/parallel design. The researcher distributes questionnaires to 30 respondents and the data will be processed using SPSS. In addition, the researcher will conduct interviews with 5 respondents to provide interpretations of the research results both quantitatively and qualitatively. The results of the data analysis show that simple bookkeeping (X) has a positive effect on cash flow management (Y) and obtains a coefficient of determination of 72%. This can be interpreted that the X variable (simple bookkeeping) has a contribution effect of 72% on the Y variable (cash flow management). From the results of the interviews, it was found that so far the recording activities were carried out only to find out expenses and income and calculate profits. It was found that MSME actors only make a simple record, where the record shows the amount of purchases (capital goods) and sales (sales turnover). Until that stage alone, and even then it is not as contained in the literature or established accounting standards. That is, the financial records that are applied do not follow the stages in the accounting cycle, and these records can only be understood by the MSME actors themselves Knowledge and information regarding simple bookkeeping, is still minimal among MSME actors, so that in the future, training and assistance is needed for MSME actors, especially in the field of financial recording and reporting and efforts so that MSME actors have sufficient knowledge in carrying out their business activities.